ADVANTAGES OF USING CLOUD SERVICES TO MONITOR STUDENT LEARNING DURING THE TEACHING PROCESS - Shokir Ravshanovich Bobobekov (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses cloud technology-based on network services and how to use them to monitor student learning. It also provides a practical way to organize students' independent study of Information Security and enrich it with information resources in a Google classroom network service based on cloud technologies.